Rancangan Konversi Kredit Konsumtif menjadi Akad Murabahah pada Koperasi Warga Cipta Mas 2 - Fariza Bahari Fadliani; Djoni Djatnika; Kristianingsih Kristianingsih (Journal of Applied Islamic Economics and Finance, 2021)
The emergence of sharia cooperatives is the improvement of conventional cooperatives that are not in line with the sharia principles one of them is riba. The Sharia-economic spirit was also felt by members and managers of the Koperasi Warga Cipta Mas 2 located in Bandung Barat. The adjustment of this report primarily lies in the use of the agreement that must comply with the sharia principles that are stored in the postal gathering funds and the disbursement of funds. Adjustments are also made to the source of cooperative income that should not be derived from riba and the use of fines that should not be recognized as cooperative income. Then followed by the design of the Murabahah receivables that can be used when the Koperasi Warga Cipta Mas 2 has become a cooperative sharia. The selection of the agreement is based on the history of borrowing and the needs of members who are mostly loans for personal consumption. In this draft, the procedure was obtained for the application of Murabahah financing, installment financing, and handling problematic financing.